2020
DOI: 10.1038/s41598-020-71804-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation regulates opioid-induced respiratory depression in mice

Abstract: In the U.S., opioid prescription for treatment of pain nearly quadrupled from 1999 to 2014. The diversion and misuse of prescription opioids along with increased use of drugs like heroin and fentanyl, has led to an epidemic in addiction and overdose deaths. The most common cause of opioid overdose and death is opioid-induced respiratory depression (OIRD), a life-threatening depression in respiratory rate thought to be caused by stimulation of opioid receptors in the inspiratory-generating regions of the brain.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 78 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…Breathing behaviors and OIRD severity differ between strains of mice ( Bubier et al, 2020 ). Therefore, we sought to compare basal and morphine depressed breathing in mice with the same genetic background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breathing behaviors and OIRD severity differ between strains of mice ( Bubier et al, 2020 ). Therefore, we sought to compare basal and morphine depressed breathing in mice with the same genetic background.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other studies, we designed ours with five important features to ensure a robust conclusion. First, the OIRD comparisons were made between littermates in an effort to control for any strain specific effects on breathing and opioid sensitivity ( Bubier et al, 2020 ). Second, OIRD was defined as the comparison of breathing after IP injection of saline and morphine in the same animal to control for any within-animal specific breathing variation.…”
Section: Discussionmentioning
confidence: 99%
“…Data from previous studies showing that leptin mitigates the effects of opioids by improving upper airway patency and control of breathing suggest that decrease in mortality is mainly due to attenuation of respiratory failure [ 3 ]. However, Bubier et al did not observe a correlation between respiratory depression, recovery time and survival time in different mouse strains [ 7 ]. Thus, the adverse effects of morphine on other systems may play a role in morphine induced mortality.…”
Section: To the Editormentioning
confidence: 99%
“…Thus, the first results obtained by Bohn and co-workers on beta-arrestin 2 knockout animals were obtained on a mixed genetic background (beta-arrestin 2 knockout 129/SvJ backcrossed with C57BL6). Previous studies reported that the 129/SvJ mice have a higher sensitivity to morphine-induced antinociception ( 36 ), did not develop tolerance to morphine-induced analgesia ( 37 ) and were less sensitive to respiratory depression ( 38 ). When reassessing the pharmacological responses induced by opioids in beta-arrestin 2 knockout using an homogenous C57BL6 background, Koblich and colleagues did not find any difference in tolerance to analgesic effects of few opioids including morphine ( 39 ).…”
Section: But They Remain Mor Ligands (With Their Side Effects)mentioning
confidence: 99%